The role of organic matter chemistry in iron redox transformations, sorption to iron oxides, and wetland carbon storage - Daugherty, Ellen E., author; Borch, Thomas, advisor; Barisas, George, committee member; Conant, Richard, committee member; Neilson, James, committee member (Colorado State University. Libraries, 2018)
Organic carbon comprises a versatile and complex class of compounds that influence water quality, soil health, fate and transport of environmental contaminants, biogeochemical cycles, and climate change. Key to predicting the responses of these systems and processes to environmental change is a molecular-level understanding of how organic carbon reacts with other components of soil and water. Yet due to its complexity and that of the systems in which it is found, organic carbon dynamics remain poorly understood. In both terrestrial and aquatic environments, the reactivity and biological necessity of iron and carbon link the biogeochemical cycling of these elements. Complexation of iron by dissolved organic carbon molecules alters its solubility and oxidation-reduction behavior and may explain the persistence of reduced iron (Fe(II)) in oxic aquatic environments. By examining the coordination environment of Fe(II) complexed by dissolved organic matter (DOM) and evaluating the effects of complexation on Fe(II) oxidation, I determined that the majority of Fe(II)–DOM complexes were characterized by coordination with citrate-like ligands, which were unlikely to inhibit oxidation by molecular oxygen. Nonetheless, association with reduced organic matter could extend the lifetime of Fe(II) in oxic environments by several hours. In soils and sediments, iron minerals act as effective sorbents of organic matter, preserving substantial amounts of carbon from microbial decomposition. These interactions have increasingly been recognized as important components of carbon sequestration, yet the effects of temperature on sorption behavior remain unknown. Through several batch and continuous flow experiments, I demonstrated a positive relationship between temperature and sorption of DOM on iron oxide surfaces. The temperature sensitivity of sorption behavior varied among riverine, peat, and soil DOM types, with riverine natural organic matter sorbing and desorbing the most at all temperatures. Analyses of effluents also revealed preferential sorption of aromatic compounds during the initial stages of sorption. In soils, organic matter quantity and composition are determined primarily by the balance between plant productivity and microbial decomposition, which are in turn dependent upon climate, temperature, hydrology, nutrient availability, and soil composition. Wetlands store disproportionately large amounts of carbon, yet the processes controlling storage are poorly understood. I investigated how different environments created by the hydrology and geomorphic setting of two wetland types, depressional and slope, impacted soil organic carbon storage and composition. Results showed a prevalence of aliphatic structures in depressional wetlands, especially in deeper soils, suggestive of anaerobic decomposition processes. By comparison, carbon in slope wetlands was dominated by labile plant carbohydrates in surface soils and aromatic compounds at depth, a likely indication of less anaerobic conditions. These results demonstrate divergent pathways of organic matter processing in different hydrogeomorphic environments. In total, this work contributes to more mechanistic understandings of important carbon dynamics that influence carbon and iron cycling, climate change, and environmental health.
Keywords: iron oxides; organo-mineral associations; wetlands; organic matter; carbon cycling; temperature